2020
DOI: 10.1007/978-981-15-6648-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Lung Cancer Using Machine Learning Classifier

Abstract: Lung cancer generally occurs in both male and female due to uncontrollable growth of cells in the lungs. This causes a serious breathing problem in both inhale and exhale part of chest. Cigarette smoking and passive smoking are the principal contributor for the cause of lung cancer as per world health organization. The mortality rate due to lung cancer is increasing day by day in youths as well as in old persons as compared to other cancers. Even though the availability of high tech Medical facility for carefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 25 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Also, Li et al [19] proposed a fusion algorithm that combines handcrafted features into the features learned at the output layer of a 3D deep convolutional neural network (CNN). Patra [20] analyzed various machine learning classifier techniques to classify lung cancer into benign and malignant. Lai et al [21] trained clinical and gene expression data with improved deep neural network (DNN).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Li et al [19] proposed a fusion algorithm that combines handcrafted features into the features learned at the output layer of a 3D deep convolutional neural network (CNN). Patra [20] analyzed various machine learning classifier techniques to classify lung cancer into benign and malignant. Lai et al [21] trained clinical and gene expression data with improved deep neural network (DNN).…”
Section: Introductionmentioning
confidence: 99%
“…In their research, they observed that LR with a 7-fold cross validation regime and SVM with a 10-fold cross validation strategy outperformed the other classifiers on the UCI repository and SLCD dataset respectively. Recently, Patra [161] compared the performances of four different classical ML algorithms: RBF-NN, k-NN, NB and J48 on the Lung Cancer dataset of the UCI repository. The experimental outcomes confirmed that NN produces the best accuracy with a 10-fold cross validation technique.…”
Section: Diagnosis Report Based Methodsmentioning
confidence: 99%
“…Furthermore, since interpretation is highly reliant on prior experience, less trained radiologists have significant variability in detecting subtle lung cancers. For the detection of lung nodules, there has been significant variation in performance amongst radiologists.CT scan analysis is further complicated by the complex airway and vessel layout [12].…”
Section: Related Studymentioning
confidence: 99%